CORPORATE GOVERNANCE REGULATION IN EMERGING COUNTRIES. CASE OF ROMANIA - Claudiu George BOCEAN (Management & Marketing)
Most of the literature on corporate governance emphasizes that firms should be run in the interests of shareholders. This is a suitable objective function when markets are perfect and complete. In many emerging economies this is not the case: markets are imperfect and incomplete. Corporate governance issues are especially important in emerging countries, since these countries do not have the long-established financial institution infrastructure to deal with corporate governance issues. This paper discusses how emerging countries are dealing with corporate governance issues and the extra obstacles they have to overcome due to a lack of regulations. Romanian case study is examined.